The Effect of Survey, Connection, Read, Outline and Look Back (SCROL) Strategy to Increase Students’ Reading Comprehension of Descriptive Text in Tenth Grade of MAN 1 Takengon - Linda Fitri Ibrahim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this research is: “To know whether Survey, Connection, Read, Outline and Look Back (SCROL) strategy significantly affect to increase students’ reading comprehension of descriptive at tenth grade of MAN 1 Takengon”. The method used in this research is quantitative research with an experiment approach. For collecting data are using observation and test. The population in this research is the tenth grade students of MAN 1 Takengon with total number 221 students. Sample used in this research is X Scince2 class as the experimental class and the control class X Science1. Both of the class consist of 20 students. The result of this research based on calculation of t-test, where the value of tscore 3,8 is higher than ttable 1,9 at the level significance 0,05. It shows that the hypothesis (Ha) is accepted and the research hypothesis (Ho) is rejected. Based on the results, for suggestion teacher can apply this method in teaching reading and using appropriate technique in teaching and the learning process.